Feasibility report on the textile factory at Maiduguri North-Eastern State of Nigeria (Warsaw: POLCOMEX, 1970)
The book is about the Polish company Polcomex's interest in participation in the setting up and running the planned textile factory at Maiduguri, North-Eastern State of Nigeria.
rpm 29/01/2019
Ref.
Keywords: Feasibility Report; Textile Factory; Maiduguri; North-Eastern Nigeria; Nigeria